Sérfræðingar í hjúkrun : skilgreining, viðurkenning og nám - Kristín Björnsdóttir; Marga Thome (Félag íslenskra hjúkrunarfræðinga, 2007)
Hægt er að lesa greinina í heild sinni með því að smella á hlekkinn View/Open This paper describes the roles of specialists in nursing, ways in which their services are certified and regulated and it also discusses the characteristics of the knowledge and education that specialists in nursing require. A comprehensive literature search led to a variety of sources from a number of European countries such as the United Kingdom, Germany, Sweden, Switzerland and the Netherlands in addition to literature from North America. Important work on the clarification of specialists in nursing has also been done by International Counsil of Nurses and European Federation of Nurses Associations (EFN). Results showed that there is no current consensus on definitions, regulations, roles, education nor practice of nurse specialists between countries, neither in Europe nor in the Anglo-Saxon world. There are even large differences between regions and states of the same country. In comparison to the education of specialists in other practice oriented disciplines in Iceland, e.g. psychologists or physicians, more emphasis is placed on theoretical knowledge than on clinical experience in the education of nurse specialists in Iceland. Differences in traditions and positions with regard to preparing specialist nurses for practice are described and discussed. A number of suggestions are made regarding the development of specialist education in Iceland. Tilgangur þessarar greinar er að skýra hlutverk, starfssvið og þekkingu sérfræðinga í hjúkrun svo hægt sé að skipuleggja framhaldsnám í hjúkrunarfræði sem endurspeglar þær væntingar sem gerðar eru til þeirra. Gögnum um störf, viðurkenningu og menntun sérfræðinga í hjúkrun var safnað frá ýmsum löndum, auk upplýsinga um sérfræðinga í öðrum starfsgreinum hér á landi. Í þeim kemur fram að gerðar eru ólíkar kröfur um menntun og starfsreynslu sérfræðinga í hjúkrun eftir löndum og jafnvel svæðum innan landa og að ábyrgð og sjálfstæði sérfræðinga er mismikið. Borið saman við aðrar starfsstéttir ...